Decision support system for seismic risks - María J. Somodevilla (Journal of Computer Science and Technology, 2012)
This paper focuses on prediction and prevention of seismic risk through a system for decision making. Data Warehousing and OLAP operations are applied, together with, data mining tools like association rules, decision trees and clustering to predict aspects such as location, time of year and/or earthquake magnitude, among others. The results of the data mining and data warehouse application help to confirm uncertainty about problems behavior in decision making, related to the prevention of seismic hazards.